Applying ISO:31000:2018 as Risk Management Strategy on Heavy Machinery Vehicle Division - Wicaksono, Ananto Yusuf; Yusron, Rifky (International Journal of Science, Engineering, and Information Technology, 2020)
The operation of heavy machinery vehicles and extensive project site areas are constrained in a general contractor services business, they need risk management to overcome obstacles that interfere project.. Transporting heavy machinery vehicles from one project location to another project site using low bed movers have a risk. Ideal condition for company heavy machinery vehicle with minimum transport. Despite their completion to represent low budget to manage project, it mitigation time, embarkation and debarkation is a challenge too. The aim of this research is to observe level of effectiveness in applying ISO 31000:2018 risk management standard in heavy machinery operations. We apply expert judgment in risk assessment techniques using questioner. This was distributed to respondents who had experience operating heavy machinery vehicles for at least 3 years. Heavy machinery vehicle operators must have enough experience and maintenance of heavy machinery just conduct routinely based on a manual book. From the results of risk identification,  there are 20 risks. Based on the results of the risk assessed from probability and impact variables, damaged risk to the undercarriage parts (R12)  as a top priority treatment risk. Risk management will be identified as mitigation strategies based on 5 aspects. They are avoided risk, risk control, separating risk, moving risk and accepting risk. Results of identification from treatment strategies will be assessed based on mitigation duration and mitigation costs, to find out the most optimal strategy for dealing with these risks. It can concluding assessment of risk management strategies well, if mitigation strategies separate risks. is the most optimal mitigation strategy.